Bubbles in the Singapore property market : an econometric prospective. - Chia, Swee Kuen. (2008)
In this paper, we attempted to model dynamic movement in prices, borrowing an earlier model on the US market, using both fundamental variables as prescribed by general urban economic theories as well as expectations modeled as dynamic adjustments. The dynamic component performed well as expected, accounting for 60% of property price change, thus providing empirical evidence of the role of expectations and bubbles in the local property market.